The theme of Don Juan in David Samoylov’s literary production - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2011)
The aim of this article is to analyse four different poems by David Samoylov, a 20th century Russian writer: The End of Don Juan, The Old Don Juan, The Young Don Juan and The Comandorov’s Footsteps. All of them are new interpretations of the Don Juan story. Thanks to the new plot solutions and to the literary dialogue with Pushkin and Blok, Samoylov’s works are interesting and valuable contribution to the literary versions of the Don Juan theme.